Social signaling and interorganizational relationships: Lessons learned from the professional sports industry - Posthuma, Richard A.; Flores, Gabriela L.; Barlow, Matthew A.; Dworkin, James B. (Business horizons, 2018)
In today’s connected economy, interorganizational relationships are increasingly important. Whether government-to-government, political party-to-political party, business-to-business, department-to-department, or some other interorganizational pairing, these relationships can provide organizations with signals used to identify and better respond to changes in their environment and in their interorganizational relationships. This enables astute organizations to not only understand how others will interpret the social signals they send, but also to shape those signals in ways that will improve their interorganizational relationships. We illustrate this herein, using the public and readily recognizable relationships involved with labor relations in the professional sports industry. We show how social signals can explain the way organizations change and adapt to their environments, and how these changes send messages to related organizations. Finally, we provide a set of recommended advice for managers based on this case analysis.